Anti-inflammatory action and intraocular kinetics of bromfenac in anterior uveitis depending on the composition of topical formulation - E. V. Blinova; P. A. Lyabushev; E. A. Litvin; D. S. Blinov; A. A. Galchin; M. V. Shikh; I. S. Struts; K. D. Blinov; S. D. Yudina; O. V. Vasilkina; S. E. Zotov; E. V. Shikh (Российский офтальмологический журнал)
Purpose: a comparative study of the main characteristics of the anti-inflammatory effect of the ophthalmic dosage form (ODF) of bromfenac — the drug Broxinac and analogues, their local bioavailability, biodistribution and intraocular pharmacokinetics during the inflammatory process in the anterior segment of the rabbit eye.Material and methods. The studies were performed on 40 sexually mature male rabbits of the “Soviet Chinchilla” breed with an experimental model of carrageenan anterior uveitis. The anti-inflammatory and local irritant effect on the cornea, bioavailability and intraocular pharmacokinetics in the anterior chamber humor of ODF - bromfenac drops with various auxiliary components when instilled into the conjunctival sac were determined.Results. Broxinac, containing 0.05 mg/ml benzalkonium chloride as an auxiliary substance, exhibits more pronounced anti-inflammatory properties than existing analogues containing benzalkonium chloride at a concentration of 0.01 mg/ml or not containing it at all. The drug does not cause a local irritant effect when administered every 12 hours for 10 days 1 drop into the conjunctival sac of the eye of an awake rabbit, only minor signs of irritation in the form of closing of the eyelids in some rabbits were noted. When using comparison drugs containing 0.01 mg of the aforementioned preservative, the severity of the local irritant reaction fluctuated in a fairly wide range: from moderate to pronounced. It was established that the dosing form of Broxinac creates high peak concentrations in the anterior chamber humor and vitreous body, which remain within the therapeutic limits for at least 12 hours regardless of the presence of uveitis, with a half-life from the anterior chamber humor, depending on the presence of pathology, from 79 to 89 minutes.Conclusion. The ability of auxiliary components to change the pharmacology of the dosing form is the basis for optimizing the local bioavailability and pharmacodynamics of bromfenac as the active substance of the drug Broxinac. An increase in the concentration of benzalkonium chloride to 0.05 mg / ml (which is 5 times higher than that of the selected analogues) facilitates the passage of bromfenac through the tissue barrier of the eye and prevents presystemic elimination.